Case Report: Immune Checkpoint Inhibitors as a Single Agent in the Treatment of Metastatic Cervical Cancer - Anipindi, Manasa; Smith, Ryan J.; Gilani, Madiha (Frontiers in Oncology, 2022)
The incidence of cervical cancer has decreased in recent years due to widespread vaccination and routine screenings. It can be treated successfully, and the prognosis is also excellent if detected early. However, the 5-year survival rate for patients with stage IV cervical cancer is only 17% even with aggressive systemic chemotherapy. With the FDA approval of immunotherapy, the prognosis has improved. We present a patient with stage IV cervical cancer who could not tolerate platinum-based chemotherapy and bevacizumab, so she was started on immune checkpoint inhibitor as her tumor was 100% programmed death cell ligand-1 (PDL-1) positive. She survived more than 2 years since the diagnosis of stage IV cervical cancer without any significant side effects. Based on our patient’s response, the use of immune checkpoint inhibitors as a single agent needs further research and probably can be considered in patients with stage 4 cervical cancer who cannot tolerate standard chemotherapy.